Prevention of UVB radiation-induced oxidative stress in mice by topical administration of Azadirachta indica (neem) extract - Renata Micheli Martinez; Clara Ruiza de Souza; Cristina de Paula Barros de Melo; Marcela Maria Baracat; Nilton Syogo Arakawa; José Carlos Duarte; Waldiceu Aparecido Verri Jr; Rúbia Casagrande; Sandra Regina Georgetti (São Paulo State University (UNESP), 2020)
Neem tree (Azadirachta indica A. Juss. fam. Meliaceae) has been extensively employed to combat diverse pathologies. Moreover, it has been described that its leaf extract present anticarcinogenic action. Thus, the neem extract (NE) chemical and antioxidant properties was evaluated, and also, the capacity of two dermatological formulations incorporated with neem extract (F1 and F2) to avoid oxidative UVB-induced skin injury in hairless mice. NE constituents were investigated and free radical scavenging ability were determined by different methods in vitro. Skin from mice treated with F1 and F2 and submitted to UVB radiation were tested for different parameters of inflammation and oxidative injury. Results show that the NE polyphenol and flavonoid content were 135.30 and 37.12mg/g, respectively. High performance liquid chromatography (HPLC) results demonstrated the existence of azarachtin, rutin, ursolic acid and tannic acid. NE presented scavenging ability by ABTS radical, ferric-reducing antioxidant power (FRAP), inhibition of lipid peroxidation and iron chelation. In vivo, it was observed that mice treated with F1 and F2 showed amelioration of the inflammation by reducing UVB induced skin edema. However, only samples from animals treated with F1 had lower neutrophil recruitment (measured by myeloperoxidase activity), and returning the oxidative status to baseline levels in parameters such as reduced glutathione level, ferric reducing ability (FRAP), and scavenging of free radical (ABTS). Concluding, NE demonstrated a good antioxidant property in vitro, and the data suggest the use of NE added F1 to prevent skin damage caused by UVB irradiation.